On hot-spot traffic pattern of TESH network - Rahman, M.M. Hafizur; Inoguchi, Yasushi; Sato, Yukinori; Miura, Yasuyuk; Horiguchi, Susumu (2008)
In this paper, we present a deadlock-free routing algorithm for the Tori connected mESH (TESH) network using 2 virtual channels - 2 being the minimum number for dimension-order routing - and evaluate the networks dynamic communication performance under the hot-spot traffic pattern, using the proposed routing algorithm. We evaluate the dynamic communication performance of TESH, mesh, and torus networks by computer simulation. It is shown that the dynamic communication performance of the TESH network is better than that of the mesh and torus networks. It is also shown that the relative difference in maximum throughput between torus and TESH networks decreases with the increase of hot spot traffic.